Method Validation on Functional Groups Analysis of Geopolymer with Polyvinyl Chloride (PVC) as Additive Using Fourier Transform Infrared (FT-IR) - Sulistyani, Martin; Kusumastuti, Ella; Huda, Nuril; Mukhayani, Feri (Indonesian Journal of Chemical Science, 2021)
Fourier transform infrared (FT-IR) transmission spectroscopy is a method of analyzing functional groups on a compound that is simple, economical, and non-destructive. Geopolymers with PVC synthetic fiber additives are considered to have complete functional groups representing organic and inorganic compounds. The purpose of this study was to validate the functional group analysis method on geopolymers using FT-IR. To analyze the typical peaks of the spectra of the geopolymer compound, KBr pellets were prepared with 7 sample variations (0.25 mg; 0.50 mg; 0.75 mg; 1.00 mg; 1.25 mg; 1.50 mg; and 1. ,75 mg) on ​​the addition of KBr up to 16 mg interday and intraday for 3 consecutive days. The FT-IR spectroscopy method was validated with the parameters of linearity, detection limit (LoD), quantization limit (LoQ), accuracy, and precision. The analytical method applied is linear with the measured sample concentration range. The absorbance at wave number 986 cm-1 as the Si-O-Si absorption peak was chosen for method validation. From the results of the analysis, the regression coefficient (R2) is 0.9938 for geopolymers and 0.9923 for geopolymers with PVC as an additive. The analytical method that has been carried out shows that FT-IR spectroscopy is precise and accurate for measuring the spectrum of geopolymers and geopolymers with PVC additives.